2013
DOI: 10.1002/jssc.201201142
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting drug adsorption on beta zeolites

Abstract: The adsorption behaviour of three commonly used drugs, namely ketoprofen, hydrochlorothiazide and atenolol, from diluted aqueous solutions on beta zeolites with different SiO2/Al2O3 ratio (i.e. 25, 38 and 360) was investigated by changing the ionic strength and the pH, before and after thermal treatment of the adsorbents. The selective adsorption of drugs was confirmed by thermogravimetry and X-ray diffraction. The adsorption capacity of beta zeolites was strongly dependent on both the solution pH and the alum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 49 publications
3
44
0
Order By: Relevance
“…It can be seen that the kinetics of the adsorption process was very fast; the equilibrium was reached in about 10 min. Similar behaviors were also observed for the adsorption of other aqueous contaminants, such as dichloroethane and toluene onto ZSM-5 and Y zeolites [5][6][7][8][9][10]13].…”
Section: Adsorption Isotherms From Aqueous Solutionssupporting
confidence: 65%
See 2 more Smart Citations
“…It can be seen that the kinetics of the adsorption process was very fast; the equilibrium was reached in about 10 min. Similar behaviors were also observed for the adsorption of other aqueous contaminants, such as dichloroethane and toluene onto ZSM-5 and Y zeolites [5][6][7][8][9][10]13].…”
Section: Adsorption Isotherms From Aqueous Solutionssupporting
confidence: 65%
“…We have previously verified [5][6][7][8][9][10]13] that uptake data of the investigated zeolites can be fitted by the pseudo-second order model as:…”
Section: Adsorption Isotherms From Aqueous Solutionsmentioning
confidence: 94%
See 1 more Smart Citation
“…In particular, the thermal treatment considerably increases the adsorption efficiency of all BEAs toward TOL in the low concentration range. This finding has also been observed also for polar compounds such as pharmaceuticals [6]. It has been suggested that part of the adsorption properties of BEA zeolites originates from faults in the zeolitic structure [35].…”
Section: Adsorption From Aqueous Solutionssupporting
confidence: 57%
“…Among several techniques developed for BTEX removal from waters, adsorption is one of the most efficient methods, thanks to satisfactory efficiencies even at low concentrations [3], easy operation and low cost [4]. Recently, high-silica zeolites have been shown to be environmental friendly materials able to efficiently sorb several organic pollutants from water, such as pharmaceuticals [5][6][7], polycyclic aromatic hydrocarbons [8], phenols [9] and petrol-derived compounds [10][11][12].…”
Section: Introductionmentioning
confidence: 99%